A Canonical Analysis of Successful vs. Unsuccessful High Schools: Accommodating Multiple Sources of Achievement Data in School Leadership - Robert C. Knoeppel; James S. Rinehart (Educational Considerations, 2010)
What distinguishes successful schools from unsuccessful schools? This question has relevance for the practice of educational leadership as well as the preparation of leaders.
Keywords: Educational; leadership; accommodating; data; literature; effective; schools; Canonical Analysis; equality; instructional